2018
DOI: 10.1021/acs.iecr.8b02215
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Development of Efficient Electro-Fenton Reactors for Soil Washing Wastes through Microfluidic Cells

Abstract: This work focuses on the coupling of three different approaches into the same reactor at 11 the same time: microfluidic cells, anodic oxidation with diamond anodes and an electro-12 Fenton process. In order to supply oxygen a jet aerator was used and a CB/PTFE 13 Duocel ® Al foam cathode was installed to promote the formation of hydrogen peroxide. 14 This novel concept is applied for the direct treatment (without the addition of salts or 15 other reagents) of soil washing wastes obtained in the remediation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…This same behavior was observed in the EF tests at lab scale. Also, one of the previous studies using the MF-FT coupled to the jet aerator available in the literature concluded, after testing current densities from 10 to 50 mA cm −2 (corresponding with 0.33 to 1.65 A, calculated with the wet cross section of the electrodes specified in the article), that increasing the current density reduced the efficiency of the EF treatment [13].…”
Section: Electro-fenton Treatment At Bench Scalementioning
confidence: 97%
See 1 more Smart Citation
“…This same behavior was observed in the EF tests at lab scale. Also, one of the previous studies using the MF-FT coupled to the jet aerator available in the literature concluded, after testing current densities from 10 to 50 mA cm −2 (corresponding with 0.33 to 1.65 A, calculated with the wet cross section of the electrodes specified in the article), that increasing the current density reduced the efficiency of the EF treatment [13].…”
Section: Electro-fenton Treatment At Bench Scalementioning
confidence: 97%
“…To the best of the authors' knowledge, there are only two previous studies that report the use of a MF-FT reactor combined with a jet aerator for an EF treatment at bench scale [10,13]. However, in both cases the EF assays were performed with homogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Clopyralid is an organochlorinated herbicide from the class of the pyridine compounds (i.e., pesticides derived from picolinic acid) that have widespread use for control broadleaf weeds and woody plants [2]. Given its recalcitrance and toxicity, many research efforts have been devoted to study effective technologies capable of removing this type of contaminant from aqueous solution [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The degradation and mineralization rate of the AO process using BDD anode can also be increased by combination with other processes such as electro-Fenton, [40][41][42] sonolysis [43][44][45][46] or photolysis. [43,[45][46][47][48][49] Such approach allows for providing an additional source of * OH and other oxidant species.…”
Section: Process Efficiencymentioning
confidence: 99%